A Metal–Organic Framework derived CuxOyCz Catalyst for Electrochemical CO2 Reduction and Impact of Local pH Change. Issue 43 (23rd September 2021) - Sikdar, Nivedita; Junqueira, João R. C.; Dieckhöfer, Stefan; Quast, Thomas; Braun, Michael; Song, Yanfang; Aiyappa, Harshitha B.; Seisel, Sabine; Weidner, Jonas; Öhl, Denis; Andronescu, Corina; Schuhmann, Wolfgang
Abstract: Developing highly efficient and selective electrocatalysts for the CO2 reduction reaction to produce value‐added chemicals has been intensively pursued. We report a series of Cu x O y C z nanostructured electrocatalysts derived from a Cu‐based MOF as porous self‐sacrificial template. Blending catalysts with polytetrafluoroethylene (PTFE) on gas diffusion electrodes (GDEs) suppressed the competitive hydrogen evolution reaction. 25 to 50 wt % teflonized GDEs exhibited a Faradaic efficiency of ≈54 % for C2+ products at −80 mA cm −2 . The local OH − ions activity of PTFE‐modified GDEs was assessed by means of closely positioning a Pt‐nanoelectrode. A substantial increase in the OH − /H2 O activity ratio due to the locally generated OH − ions at increasing current densities was determined irrespective of the PTFE amount. Abstract : A series of nanostructured Cu x O y C z electrocatalysts were synthesized from Cu‐based MOF precursors. The catalysts were blended with PTFE for preparation of gas diffusion electrodes (GDEs) to suppress hydrogen evolution by preventing electrowetting process. The local OH − ion activities of working GDEs were determined in absence and presence of PTFE to exclude interference in local OH − ion generation in the vicinity of GDE by PTFE.